2010
DOI: 10.1111/j.1745-4603.2010.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Skull Vibration During Chewing of Crispy Food

Abstract: When we chew crispy food, the jaw decelerates and accelerates as a result of resistance and breakage of food particles, and a characteristic sound of the breakage of the food particles is produced. Our aim was to investigate how physical responses, in the form of vibrations, change during chewing. This will give an impression of how food characteristics change during the chewing process. Force resistance and sound emission of three crispy foods (biscuits) and one noncrispy food (cake) were determined with a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…While testing using humans provides a direct link with sensory perception, it has been shown that sounds produced during instrumental testing of crisp products are strongly correlated with the bone-conducted vibrations occurring when an individual bites into the product (van der Bilt et al, 2010). This research provides support for previously published research presenting sounds recorded during mechanical breakage of crisp products (Chen et al, 2005;Varela et al, 2006;Primo-Martin et al, 2009;Salvador et al, 2009;Saeleaw and Schleining, 2010).…”
Section: Measures Of Soundsupporting
confidence: 77%
“…While testing using humans provides a direct link with sensory perception, it has been shown that sounds produced during instrumental testing of crisp products are strongly correlated with the bone-conducted vibrations occurring when an individual bites into the product (van der Bilt et al, 2010). This research provides support for previously published research presenting sounds recorded during mechanical breakage of crisp products (Chen et al, 2005;Varela et al, 2006;Primo-Martin et al, 2009;Salvador et al, 2009;Saeleaw and Schleining, 2010).…”
Section: Measures Of Soundsupporting
confidence: 77%
“…1C). Furthermore, skull vibrations gradually decreased upon further chewing because the food particles are fragmented by the teeth and mixed with saliva to form a bolus that can be swallowed (9–11). Just before swallowing, the skull vibrations produced by chewing had decreased to the level recorded when chewing a non‐crispy cake (11).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the participants were uncertain about what they were chewing, which resulted in longer cycle durations. In a later phase, chewing sounds and vibrations were no longer present as the crispy biscuits had been transformed into a well‐moistened food bolus (11). The effects of visual masking were present at the beginning, as well as halfway through the chewing process, while just before swallowing the effects of visual masking had disappeared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, most of these studies used a microphone to detect the sound of the sample breaking (see Duizer, 2001;Taniwaki and Sakurai, 2010a for review). The microphone method for recording mastication sounds from the panelists has several drawbacks for quantitative and reproducible evaluation of food texture, such as variations in the microphone performance (Chen et al, 2005), the experimental conditions (room size, arrangement of auditory equipment, and environmental noise), the resonant frequencies of the mouth cavity and the skull bone connected to the mouth (van der Bilt et al, 2010), and the quantity and rate of saliva during mastication (Szczesniak, 2002). Most of the above drawbacks stem from the inevitable variation between the individual panelists.…”
Section: Introductionmentioning
confidence: 99%